2018
DOI: 10.1021/acs.jpcc.8b05499
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Application of XPS and DFT to Investigate Metal Oxide Surface Catalysis

Abstract: To investigate metal oxide surface catalysis, determining an appropriate Hubbard U-correction term is a challenge for the density functional theory (DFT) community and identifying realistic reaction intermediates and their corresponding X-ray photoelectron spectroscopy (XPS) shifts is a challenge for experimental researchers, when these methods are used independently. In this study, using CuO as a model transition metal oxide, we demonstrate that when DFT and XPS are applied synergistically, the determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 74 publications
5
82
0
Order By: Relevance
“…This finding might be explained by the highest content in transition metals of the chernozem soil (Table S1). Indeed, as reported previously, transition metal oxides promote the formation of • OH (Amaniampong et al 2018(Amaniampong et al , 2019Trinh et al 2018;Jia and Wang 2013).…”
Section: Generation Of Reactive Oxygen Speciessupporting
confidence: 73%
“…This finding might be explained by the highest content in transition metals of the chernozem soil (Table S1). Indeed, as reported previously, transition metal oxides promote the formation of • OH (Amaniampong et al 2018(Amaniampong et al , 2019Trinh et al 2018;Jia and Wang 2013).…”
Section: Generation Of Reactive Oxygen Speciessupporting
confidence: 73%
“…Furthermore, XPS binding energy shift calculations using the slab model approach are common in the literature; Refs. [5,[35][36][37][38][39][40] give representative examples of the use of slab models for XPS. We have shown that the VCA approach represents a safe way to avoid artifacts related to the screening by the added half an electron in the conduction band and we have shown that these artifacts can result in notable errors, ∼0.5 eV in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive understanding on the electronic interaction at the interface of the thick electrodes was studied using density functional theory (DFT) calculations. [30,47] The electron density difference (EDD) provided valuable information on the electron interactions within the components of each hybrid. The cluster models of NiO, Ni 2 P, CuO and Cu 3 P for DFT simulations are shown in Figure S7, Supporting Information.…”
Section: Electronic Interactions-density Functional Theory Studiesmentioning
confidence: 99%